PEMANFAATAN HUNIAN UNTUK FUNGSI KOMERSIAL DI LINGKUNGAN PADANGTEGAL TENGAH, UBUD - I Dewa Gede Putra; Ida Ayu Armeli; Ngakan Putu Sueca (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2014)
Abstract The Ubud community residential units, especially in the Padangtegal Tengah environment have an important role as a place for shelter, socializing and performing religious rituals. Due to the modernization and development of tourism in the study area, residential units also developed into commercial functions resulting in changes in residential land use. The purpose of this study was to establish a study area, and (1) understand commercial typologies and management functions, (2) establish the occupancy use for commercial functions as well as its impact. Of the cases studied, an average of 19 percent of the floor area building capacity is used for commercial functions out of the residential land area. Consequently, spaces become functionally modified or adjusted to suit the present conditions, but some are retained. Commercial functions are able to support incomes, which increased well-being and housing consolidation. The function of traditional space in the residential core is retained, but the adaptations and modifications were carried out on land that has not been used previously, such as the area of the front and the back of the residential units. Due to modernization, the mindset of the people has changed, affecting residential land use. Hence economic rationality is changing both traditional attitudes and spatial functions in the area. Keywords: land use, traditional house, commercial function Abstrak Unit hunian masyarakat Ubud khususnya di Lingkungan Padangtegal Tengah memiliki peran penting sebagai tempat untuk bernaung, bersosialisasi dan melakukan ritual agama. Dengan adanya modernisasi dan perkembangan pariwisata pada wilayah studi, unit hunian turut berkembang menjadi fungsi komersial sehingga terjadi kecenderungan pergeseran dan perubahan pemanfataan lahan hunian. Tujuan dari penelitian ini untuk (1) mengetahui dan memahami jenis dan pengelolaan fungsi komersial, (2) memahami  pemanfaatan hunian untuk fungsi komersial serta dampaknya di wilayah studi. Rata-rata, 19 persen kapasitas luas lantai bangunan digunakan untuk fungsi komersial berbanding luas lahan hunian. Konsekuensinya, telah terjadi modifikasi keruangan berdasarkan fungsi untuk mengakomodasi kondisi kekinian. Fungsi komersial dapat menunjang pendapatan yang berdampak pada peningkatan kesejahteraan dan konsolidasi hunian. Fungsi ruang tradisional pada bagian inti hunian masih dipertahankan, namun adaptasi dan modifikasi dilakukan pada lahan yang belum dimanfataankan sebelumnya, seperti area depan dan belakang unit hunian. Modernisasi telah mempengaruhi cara pandang masyarakat dalam memanfaatkan lahan huniannya. Cara pikir secara ekonomis telah merubah tingkah lalu tradisional dan fungsi spasial pada area ini. Kata kunci: tata guna lahan, hunian tradisional, fungsi komersial